Nutrient cycling and carbon dynamics in an early successional forest in Turrialba, Costa Rica - Rojas Alvarado, Carlos (2025)
The quantification of nutrient cycling is important to generate technical guidelines for the conservation and management of tropical forests under the scope of global phenomena such as climate change. The present study provides the baseline data on the current fluxes of nutrients in a 30-year-old forest system that started as a reforested subsoil mount generated when a dam project was built in the general area of Turrialba, Costa Rica. Tree growth and nutrient fluxes were determined by measuring trees and using litterfall beds between 2018-2020. Carbon and nitrogen displayed values that can be linked to the history of reforestation in the studied location and demonstrated the fast and resilient dynamics of nutrients in tropical settings after the assisted reforestation was implemented. Other nutrients showed values within expected ranges and point out that the studied forests are the product of a series of appropriate technical decisions that have allowed the system to develop that way it did.